GERAK MUSLIMAH DI ANTARA MARAKNYA FEMINISME DAN ISU RADIKALISME: ANALISIS PEDAGOGI - Aminah Aminah (AN-NISA, 2018)
There are various styles of feminism that have been developing today. Generally, there are terms called classic feminism and contemporary feminism. Classical feminism consists of liberal, Marxist, Radical, and Socialist feminism and they tend to be atheistic. Whereas contemporary feminism that is increasingly developing in almost all parts of the world is the third world feminism, multicultural feminism, religion feminism, and ecofeminism. This contemporary feminism includes atheists and theists. This discussion of feminism are explored in this article  by interpreting freedom and equality between the Indonesian and Islamic contexts. On the other hand, the issue of radicalism is an issue that is widely discussed with the existence of several events that lead to terrorism and the desire to establish a system of caliphate on the earth of the motherland. Deradicalization of radicalism  is characterized by selfishness, symbolism, and closed textual corpus. They should be transformed into a more moderate understanding. Therefore, as Indonesian moslem women, these two things need to be explored further because they affect women as the first madrasa and  the nation pillars. Moslem women must be equipped with several important components in positioning themselves as a’ whole person’ in this millennial century. Those components are knowing the purpose of creation, building world views, recognizing self-potential, and becoming productive individuals in the domestic and social spheres. The creation of an Indonesian Moslem woman with a firm, virtuous, productive and knowledgeable principle is a nation milestone as a daughter, mother, wife and public sector. The women who become ‘ a whole person’ will be able to contribute in overcoming religious and national polemics.Abstract               There are various styles of feminism that have been developing today. Generally, there are terms called classic feminism and contemporary feminism. Classical feminism consists of liberal, Marxist, Radical, and Socialist feminism and they tend to be atheistic. Whereas contemporary feminism that is increasingly developing in almost all parts of the world is the third world feminism, multicultural feminism, religion feminism, and ecofeminism. This contemporary feminism includes atheists and theists. This discussion of feminism are explored in this article  by interpreting freedom and equality between the Indonesian and Islamic contexts.               On the other hand, the issue of radicalism is an issue that is widely discussed with the existence of several events that lead to terrorism and the desire to establish a system of caliphate on the earth of the motherland. Deradicalization of radicalism  is characterized by selfishness, symbolism, and closed textual corpus. They should be transformed into a more moderate understanding.               Therefore, as Indonesian moslem women, these two things need to be explored further because they affect women as the first madrasa and  the nation pillars. Moslem women must be equipped with several important components in positioning themselves as a’ whole person’ in this millennial century. Those components are knowing the purpose of creation, building world views, recognizing self-potential, and becoming productive individuals in the domestic and social spheres.               The creation of an Indonesian Moslem woman with a firm, virtuous, productive and knowledgeable principle is a nation milestone as a daughter, mother, wife and public sector. The women who become ‘ a whole person’ will be able to contribute in overcoming religious and national polemics.